Development of Multirepresentation-Based Learning Videos on the Material of Physical Properties of Alcohols and Ethers - Maulidiyah, Hanna Rohmatul; Muharini, Rini; Ulfah, Maria; Enawaty, Eny; Sasri, Risya (Journal of The Indonesian Society of Integrated Chemistry, 2024)
The topic of the physical properties of alcohol and ether compounds is often perceived as challenging by students due to its abstract nature. Consequently, the development of effective learning media is essential to address these difficulties. This study aims to develop a multirepresentation-based instructional video that illustrates the impact of intermolecular forces on the boiling points of alcohols and ethers. The research utilized the 4D model by Thiagarajan, comprising four stages: Define, Design, Develop, and Disseminate. However, this study was limited to the Develop stage. The research instruments included validation sheets and response questionnaires, employing indirect communication measurement techniques. The validity assessment involved three experts evaluating various aspects of the product, while the response test was conducted with 29 students. Data from the validation results were analyzed using the Content Validity Index (CVI), where the instructional video achieved a CVI score of 1.00, indicating very high validity. Student responses demonstrated a satisfaction rate of 85.98% (very good) in the limited trial and 83.57% (very good) in the main trial. In conclusion, the multirepresentation-based instructional video is a highly valid and effective tool that can be utilized in teaching the physical properties of alcohols and ethers.